The Impact of Lifecourse Socioeconomic Position on Cardiovascular Disease Events in African Americans: The Jackson Heart Study. Issue 6 (June 2015) - Gebreab, Samson Y.; Diez Roux, Ana V.; Brenner, Allison B.; Hickson, DeMarc A.; Sims, Mario; Subramanyam, Malavika; Griswold, Michael E.; Wyatt, Sharon B.; James, Sherman A.
Abstract : Background: Few studies have examined the impact of lifecourse socioeconomic position (SEP) on cardiovascular disease (CVD) risk among African Americans. Methods and Results: We used data from the Jackson Heart Study (JHS) to examine the associations of multiple measures of lifecourse SEP with CVD events in a large cohort of African Americans. During a median of 7.2‐year follow‐up, 362 new or recurrent CVD events occurred in a sample of 5301 participants aged 21 to 94. Childhood SEP was assessed by using mother's education, parental home ownership, and childhood amenities. Adult SEP was assessed by using education, income, wealth, and public assistance. Adult SEP was more consistently associated with CVD risk in women than in men: age‐adjusted hazard ratios for low versus high income (95% CIs), 2.46 (1.19 to 5.09) in women and 1.50 (0.87 to 2.58) in men, P for interaction=0.1244, and hazard ratio for low versus high wealth, 2.14 (1.39 to 3.29) in women and 1.06 (0.62 to 1.81) in men, P for interaction=0.0224. After simultaneous adjustment for all adult SEP measures, wealth remained a significant predictor of CVD events in women (HR=1.73 [1.04, 2.85] for low versus high). Education and public assistance were less consistently associated with CVD. Adult SEP was a stronger predictor of CVD events in younger than in older participants (HR for high versus low summary adult SEP score 3.28 [1.43, 7.53] for participants ≤50 years, and 1.90 (1.36 to 2.66) for participants >50 years, P for interaction 0.0846). Childhood SEP was not associated with CVD risk in women or men. Conclusions: Adult SEP is an important predictor of CVD events in African American women and in younger African Americans. Childhood SEP was not associated with CVD events in this population.